Effectiveness of Childbirth Self-Efficacy Enhancing Classes on Labor Length and Outcomes among Egyptian Primiparous Women: A Quasi-Experimental Study - Azza Ibrahim Abd El-Kader PhD, MSC (SAGE Publishing, 2024)
Introduction Childbirth self-efficacy has repeatedly been shown to raise satisfaction with childbirth, reduce the need for analgesic, and promote the use of different childbirth alternatives. However, the measures to improve the childbirth self-efficacy had rarely been investigated among Egyptian primiparous women. Aim The aim of this study is to evaluate the effectiveness of childbirth self-efficacy enhancing classes on labor length and outcomes among Egyptian primiparous women. Methods A quasi-experimental research approach was carried out on prospective, consecutive sample of 148 pregnant women at the end of pregnancy. A prenatal education study group (n = 74) and a control group receiving standard antenatal care (n = 74) make up the first and second groups, respectively. Between October 2021 and October 2022, the study was conducted at the antenatal clinic. The following four tools were employed to fulfill the study's objective: A structured interviewing form, a childbirth self-efficacy inventory, a follow-up checklist for monitoring maternal and neonatal outcomes during labor, and three antenatal education sessions to boost childbirth self-efficacy are all examples of tools that can be used. All statistical analyses were performed using SPSS for windows version 20.0 Results Approximately 68.9% of women in the experimental group gave birth vaginally, compared to 29.7% of those in the control group with (p = .001), according to the study's findings. In the experimental group, regular labor took an average of 8 to 12 h, but it took more than 12 h in the control group. Birth weight (>3000g) in the experimental group compared to (2000-3000 g) in the control group, as well as the Apgar score at 1 min and 5 min, were highly statistically significance between two groups with (p = .001). The means±SD of the childbirth self-efficacy result scores were better in the study group than in control groups regarding length of delivery and vaginal delivery (248.2 ± 19.4 versus 144.6 ± 21.6 and 250.1 ± 18.2 versus 137.9 ± 21.5, respectively). Conclusion According to the findings of this study, antenatal education classes have a real chance of assisting primiparous women in increasing their childbirth self-efficacy and improving maternal and neonatal outcomes.